Modeled responses to training and taper in competitive swimmers - Mujika, I.; Busso, T.; Lacoste, L.; Barale, F.; Geyssant, A.; Chatard, J. C. (Medicine & Science in Sports & Exercise, 1996)
This study investigated the effect of training on performance and assessed the response to taper in elite swimmers (N = 18), using a mathematical model that links training with performance and estimates the negative and positive influences of training, NI and PI. Variations in training, performance, NI, and PI were studied during 3-, 4-, and 6-wk tapers. The fit between modeled and actual performance was significant for 17 subjects; r2 ranged from 0.45 to 0.85, P < 0.05. Training was progressively reduced during tapers. Performance improved during the first two tapers: 2.90 +/- 1.50% (P < 0.01) and 3.20 +/- 1.70% (P < 0.01). Performance improvement in the third taper was not significant (1.81 +/- 1.73%). NI was reduced during the first two tapers (P < 0.01 and P < 0.05, respectively), but not during the third. PI did not change significantly during tapers. Thus, the present results show that the model used is a valuable method to describe the effects of training on performance. Performance improvement during taper was attributed to a reduction in NI. PI did not improve with taper, but it was not compromised by the reduced training periods.